Theory for three path experiments - Lee, Kai Sheng (2016)
The theoretical framework for an atomic slit experiment, a variation of the triple slit experiment, is developed. Such experiments test the validity of the Born rule according to which, interference fringes in the triple-slit experiment can be written in terms of fringes observed in various double and single slit experiments. The goal is to use precision of atomic experiments to improve previous experimental bounds. However, general theories and experimental procedures applicable to multi-slit experiments with different physical systems are not directly translatable. We derive ideas on how to experimentally implement a tritter and blocker, the necessary components in an atomic slit experiment.